Peran Polri Dalam Menanggulangi Tindak Pidana Penghinaan Dan/Atau Pencemaran Nama Baik Melalui Media Elektronik (Studi di Polda Sumatera Utara) - Raja Lubis, Mhd; Eddy, Triono; Sahari, Alpi (Mahesa Research Center, 2022)
The role of the National Police in tackling criminal acts of humiliation and/or defamation through electronic media is in accordance with the normative role that is in accordance with Police Law Number 2 of 2002. Technological advances show a correlation of increasing crime rates, especially in the field of cyber crime. The data collection techniques used are interviews and literature study, the type of data used in this study is primary data consisting of laws and secondary data consisting of various kinds of reading materials related to research titles such as books on cyber crimes. crime, articles, journals and literature. Based on legal research, it can be concluded as follows: Criminal policies in cyber crimes according to the context of Indonesian criminal law have been regulated in Article 27 Paragraph (3) Junto Article 45 Paragraph (3) Law no. 8 of 2011 as amended by law no. 19 of 2016 concerning Information and Electronic Transactions specifically for perpetrators of criminal acts of humiliation and or defamation through social media. The role of the National Police in tackling criminal acts of humiliation and/or defamation through electronic media, especially in the North Sumatra Regional Police, has been in accordance with its normative role, namely in accordance with Police Law Number 2 of 2002.